Climate drives global soil carbon sequestration and crop yield changes under conservation agriculture. (8th February 2020) - Sun, Wenjuan; Canadell, Josep G.; Yu, Lijun; Yu, Lingfei; Zhang, Wen; Smith, Pete; Fischer, Tony; Huang, Yao
Abstract: Conservation agriculture has been shown to have multiple benefits for soils, crop yield and the environment, and consequently, no‐till, the central practice of conservation agriculture, has rapidly expanded. However, studies show that the potential for carbon (C) sequestration in no‐till farming sometimes is not realized, let alone the ability to maintain or improve crop yield. Here we present a global analysis of no‐till‐induced changes of soil C and crop yield based on 260 and 1, 970 paired studies; respectively. We show that, relative to local conventional tillage, arid regions can benefit the most from conservation agriculture by achieving a win‐win outcome of enhanced C sequestration and increased crop yield. However, more humid regions are more likely to increase SOC only, while some colder regions have yield losses and soil C loss as likely as soil C gains. In addition to site‐specific characteristics and management, a careful assessment of the regional climate is needed to determine the potential benefits of adopting conservation agriculture. Abstract : Global patterns of soil carbon sequestration and crop yield change due to the adoption of conservation agriculture can be associated with large climatic patterns. Relative to local conventional tillage, arid regions can benefit the most from conservation agriculture by achieving a win‐win outcome of enhanced C sequestration and increased crop yield. However, more humid regions are more likely to increase SOC only, while some colder regions have yield losses and soil C loss as likely as soil C gains. In addition to site‐specific characteristics and management, a careful assessment of the regional climate is needed to determine the potential benefits of adopting conservation agriculture. See also the Commentary on this article by Hunt et al. 26, 3188–3189